2015
DOI: 10.1136/gutjnl-2014-308762
|View full text |Cite
|
Sign up to set email alerts
|

Metal or plastic stents for preoperative biliary drainage in resectable pancreatic cancer

Abstract: Dutch Trial Registry (NTR3142).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
139
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(153 citation statements)
references
References 34 publications
7
139
0
1
Order By: Relevance
“…It is controversial whether metal or plastic stents should be used for biliary obstruction caused by PC. In a recent study the use of metal stents was associated with an outcome benefit [28]. In our cohort metal stents were used more frequently than plastic ones.…”
Section: Discussionmentioning
confidence: 61%
“…It is controversial whether metal or plastic stents should be used for biliary obstruction caused by PC. In a recent study the use of metal stents was associated with an outcome benefit [28]. In our cohort metal stents were used more frequently than plastic ones.…”
Section: Discussionmentioning
confidence: 61%
“…Stent placement has been found to be associated with complications such as cholangitis and pancreatitis. Although early surgery without preoperative biliary drainage remains the treatment of choice, fully covered self-expandable metal stents may be preferred over plastic stents whenever preoperative biliary drainage is indicated [50]. In severely jaundiced patients with serum bilirubin levels ≥300 μmol/l, biliary stenting is a ppropriately recommended [51].…”
Section: Operability Assessmentmentioning
confidence: 99%
“…To be successful a screening program for pancreatic cancer needs to find and treat patients with T1N0M0 cancer with negative resection margins 50 years is a very interesting group that has so far not been subjected to screening [33]. However, the role of screening EUS/MRI even in high-risk individuals is still unclear.…”
Section: Risk Groups: How Do We Find Pancreatic Cancer Earlier?mentioning
confidence: 99%
“…The study by Adams et al [51] found that the complication rate of plastic stents was almost 7 times higher than that of metal stents, and the rate of hospitalization for stent-related complications was 3-fold higher in the plastic stent group than in the metal stent group. Moreover, the study by Tol et al [52] showed that for resectable PC, both preoperative biliary drainage-related and stent-related complication rates were smaller in the metal stent group than in the plastic stent group (24 vs. 46, and 6 vs. 31%, respectively). The above data suggest that metal stents yield a better outcome compared with plastic stents.…”
Section: Endoscopic Biliary Stenting For Obstructive Jaundicementioning
confidence: 99%